2013
DOI: 10.1111/jmp.12062
|View full text |Cite
|
Sign up to set email alerts
|

Somatometric measurements, and clinical chemistry and hematology parameters in Tibetan macaque (Macaca thibetana)

Abstract: These physiological data will provide veterinarians and researchers with baseline values to evaluate experimental results using Tibetan macaques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Morphometric measurement is an important noninvasive means for evaluating body composition and nutritional status in both human and nonhuman primate physiological research [18]. In this study, we found a similar BMI and WHR between two species, both of which are important and widely used parameters for evaluating obesity in primate studies [19,20].…”
Section: Discussionsupporting
confidence: 54%
“…Morphometric measurement is an important noninvasive means for evaluating body composition and nutritional status in both human and nonhuman primate physiological research [18]. In this study, we found a similar BMI and WHR between two species, both of which are important and widely used parameters for evaluating obesity in primate studies [19,20].…”
Section: Discussionsupporting
confidence: 54%
“…In the MIT colony, this was found to be significantly different based on postpartum status, however, none of the UT Health animals included in this assessment were postpartum (Kramer et al, 2022). This difference has not been previously associated with age in marmosets, but reduction in amylase concentrations in Tibetan macaques is associated with age, with young animals having higher amylase concentrations than old animals (Wu et al, 2014), and seems to reflect pancreatic function across age groups.…”
Section: Discussionmentioning
confidence: 60%
“…Thereby, it has great potential value in biomedical studies such as ophthalmology, obesity, metabolic disease, infectious disease, and organ transplantation (Liu et al, 2011;Ling et al, 2012;Yi et al, 2012). Recently, studies on the Tibetan macaque have primarily focused on its ethology (Zhao, 1997;Li et al, 2007;Xia et al, 2012Xia et al, , 2013, rearing, and disease prevention (Zhong et al, 2010;Wu et al, 2013). In molecular genetics, only a small number of studies on mitochondrial DNA (Li et al, 2008(Li et al, , 2009Yao et al, 2013a;Zhong et al, 2013), microsatellite DNA (Jia et al, 2011(Jia et al, , 2012, and immunity genes Yao et al, 2013b;Liu et al, 2013) have been reported.…”
Section: Introductionmentioning
confidence: 99%